G331 Manipulation under 70% nitrous in a paediatric emergency department; the effects and challenges post implementation. (12th March 2018) - Le Geyt, J; Vaughan, A; Lindisfarne, E; Crompton, T; Lazner, M; Bevan, C
Abstract : Aims: The use of manipulation under sedation (MUS) of fractures in paediatric emergency departments (PED) has become increasingly popular. Numerous studies show MUS to be safe, effective, and reducing time to manipulation, number of MUAs (manipulation under anaesthetic) and time spent in hospital. Despite this there were many barriers and safety concerns to the introduction of MUS in our hospital. A MUS protocol using 70%Nitrous for upper limb fractures was introduced in December 2016 at our PED. The aim of our study was to evaluate this service regarding safety, cost effectiveness, barriers to its use and to evaluate admissions saved. Methods: An audit was conducted of all paediatric eligible forearm and wrist fractures requiring manipulation. Data was collected from two study periods (of 5 months) before and after implementation of protocol for comparisons, February–July 2016 and same period in 2017. Data was collected on patient demographics, treatment modality, timings of presentation and treatments, and reasons eligible MUS were not undertaken. Results: In 2016, 36 patients who would have been eligible for MUS went on to have admissions and MUA. In 2017 there were 35 eligible patients, 20 who had MUS in the PED and 15 who had admission and MUA. Of the MUS group 100% were successful with no complications or requirement for further surgery and were discharged home within 4 hours. Of the 15 MUA, 11 (73%) the MUS was unable to occur because of staffing issues; presenting out-of-hours or the department being too busy. The average time of presentation of the MUS group was 16:42 and the MUA group 18:08, both out-of-hours for staffing levels. The MUS group waited an average 149 mins between presentation and definitive reduction, compared to 2.2 days in the MUA group.The cost saved per MUS case was average £1300. Conclusion: This study demonstrates MUS protocol in a PED is safe and cost efficient, providing a solution to the crises in inpatient beds and busy theatre lists. The biggest barrier to its regular implementation is staff availability out-of-hours. As a result of this study our department are creating a morning 'virtual list' within the ED, increasing MUS capacity within the current service.